1997
DOI: 10.7601/mez.48.117
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Latrodectus hasseltii (Araneae : Theridiidae) to low temperatures in Japan

Abstract: Toleranceof Latrodectus hasseltii to low temperatures(Araneae:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Although L. hasselti spiders can tolerate a wide range of temperatures, their growth may be slowed and egg sacs may cease development at low temperatures [ 70 ]. Matsuse et al [ 68 ] reported that the greatest survival rate of the spiders was at 20 °C; if under 5–10 °C, they could survive for a month but did not grow or moult. Juvenile spiders can survive short exposure (20 min) to freezing temperatures, however, the developmental zero of the egg sacs (i.e., the temperature at which egg sac development ceases) is 15–18 °C and the spiderlings do not emerge at 20 °C [ 68 , 69 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although L. hasselti spiders can tolerate a wide range of temperatures, their growth may be slowed and egg sacs may cease development at low temperatures [ 70 ]. Matsuse et al [ 68 ] reported that the greatest survival rate of the spiders was at 20 °C; if under 5–10 °C, they could survive for a month but did not grow or moult. Juvenile spiders can survive short exposure (20 min) to freezing temperatures, however, the developmental zero of the egg sacs (i.e., the temperature at which egg sac development ceases) is 15–18 °C and the spiderlings do not emerge at 20 °C [ 68 , 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Matsuse et al [ 68 ] reported that the greatest survival rate of the spiders was at 20 °C; if under 5–10 °C, they could survive for a month but did not grow or moult. Juvenile spiders can survive short exposure (20 min) to freezing temperatures, however, the developmental zero of the egg sacs (i.e., the temperature at which egg sac development ceases) is 15–18 °C and the spiderlings do not emerge at 20 °C [ 68 , 69 ]. In addition to these effects of temperature, L. hasselti are adapted to xeric conditions, so may not be able to survive in areas with high precipitation or humidity [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redback spiders can tolerate very low temperatures b Fig. 2 Cluster analysis in the CCBNR showing areas of clustering above 90, 95 and 99% confidence intervals for redback spider locations (Kamimura et al 1998) but they need shelter from extreme weather (Matsuse et al 1999) and rain and high soil moisture (Vink et al 2011). Shelter is an important factor determining their distribution in agricultural and urban landscapes in Japan (Nihei et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Redback spiders have features typical of successful invaders: they are generalist predators, able to survive long periods without food (Vink et al 2011), they can survive cold temperatures (Nihei et al 2004), females can store sperm for several years (Biosecurity NZ 2007), offspring can successfully interbreed (Forster 1984in Vink et al 2011, and female spiders produce a large number of offspring (Biosecurity NZ 2007). They are often associated with humans, typically building webs in anthropogenic environments (Matsuse et al 1999) because human structures provide them with protection from extreme weather conditions (Vink et al 2011;Biosecurity NZ 2007). It is likely that redback spiders reached New Zealand through international trade (Vink et al 2011) in shipments of steel, in vehicles, and in fresh produce and other goods (Biosecurity NZ 2007).…”
Section: Introductionmentioning
confidence: 99%